Dynamic collapse of metal self-similar hierarchical corrugated sandwich plates subject to shear and compression coupled loading - Zhang, Jianxun (2022)
Analysis of dynamic collapse response of metal self-similar hierarchical triangular corrugated sandwich plates subject to the shear loading and the shear coupled with compression is conducted. The initial collapse modes of the triangular corrugated sandwich cores are identified, in which different shear or shear-compression coupled impact velocities and various slenderness ratios of the large and small struts are considered, i.e. Euler buckling of large struts, Euler buckling of small struts, the wrinkling of large struts, the mode of combined Euler buckling of small struts with the wrinkling of large struts, and the mode of combined Euler buckling of large struts with the wrinkling of large struts. The collapse mechanism maps are then figured out with the axes representing the slenderness ratios of the large and small struts for hierarchical corrugated sandwich cores under single shear loading and combined shear and compression. In particular, the theoretically predicted collapse mechanism maps are in good agreement with the numerical results at applied velocity V0 = 1 m/s under the single shear loading and the shear coupled with compression. It is demonstrated that the velocity has insignificant influence on the dominant deformation mode of self-similar hierarchical corrugated sandwich plates for the cases of velocities V0 = 1 m/s and 10 m/s under the single shear loading and the shear coupled with compression. The designed self-similar hierarchical corrugated sandwich core has better energy absorption than traditional corrugated sandwich core subject to the single shear loading.